Towards democratic development states in Southern Africa - Muchena, Deprose; Madzwamuse, Masego; Kanengoni, Alice D.; Jauch, Herbert; Kanyenze, Godfrey (Weaver Press, 2017)
The dawn of the twenty-first century heralded an apparent change of fortunes for most sub-Saharan African economies, with annual growth averaging over 5% for fifteen years. However, this was not accompanied by structural transformation: poverty, food insecurity, unemployment and inequality persist. Structural transformation has not been - and indeed cannot be - delivered by market forces and neo-liberal economic policies; it requires a state committed to development, and to achieving it in a democratic way. To what extent do the countries of Southern Africa exhibit the characteristics of such a 'developmental state'? What steps, if any, do they need to take in order to become one? The book answers the questions with respect to South Africa, Botswana, Namibia, Zimbabwe, Angola and Malawi. Godfrey Kanyenze and his colleagues have assembled a distinguished team of writers to take the temperature of the regional political economy, and chart a path for its future development.